EFFECT OF EDUCATION LEVEL AND FAMILY SUPPORT ON DIET IN ADOLESCENTS WITH HYPERTENSION RISK WITH SELF CARE THEORY APPROACH - Bagustianto, Ridho; Fikriana, Riza; Hardiyanto (Transpublika Publisher, 2022)
Hypertension is a disease that increases every year. Diet in hypertension sufferers is still not working because many people with hypertension still have poor dietary behavior. The purpose of this study was to analyze the effect of education level and family support on diet in adolescents at risk of hypertension using the Self Care theory approach. The design of this research is Analytical Observation with Cross Sectional approach. Samples were taken using the Purposive Sampling technique with criteria according to inclusion and exclusion in Islamic Vocational Schools of Gondanglegi and NU Gondanglegi Middle Schools, Gondanglegi District, Malang Regency as many as 80 respondents. In this study, data was collected on the level of education and family support using a questionnaire sheet. The statistical test used is multiple linear regression analysis test. The results of multiple linear regression analysis revealed that the most influential variable on diet in adolescents with hypertension risk was family support with a value of (0,001) with a coefficient of -.420. Therefore, it can be seen that family support can affect diet in hypertensive adolescents, so it is necessary to have family support for hypertensive adolescents to reduce hypertension in adolescents.